Pengaruh Citra Merek, Harga dan Digital Marketing terhadap Minat Beli Ulang Konsumen UMKM Ritel Minuman HAUS - Hasanudin Hasanudin (Universitas Batanghari Jambi, 2023)
The aim of this research is to determine the influence of brand image, price and digital marketing on repurchase interest among consumers of Haus beverage retail MSMEs in Bogor Regency. Retail MSME competition is tight in selling contemporary drinks, so business people need innovation and foresight in their sales strategies. This research uses a quantitative descriptive method with on-site survey and online survey methods, which aims to see the relationship between the independent variables and the dependent variable. The sample acquisition technique in this research is nonprobability sampling with a purposive sampling technique, namely a technique for determining samples based on special considerations. The number of respondents who participated in this survey was 100 people with the criteria of having purchased HAUS beverage products more than 3 times, being at least 17 years old, following the Instagram account @hausindonesia and residing in Bogor Regency. The test tools used include data quality testing, classical assumption testing, influence testing, and hypothesis testing using SPSS 26 software. The test results show that the brand image and price variables partially have a positive and significant influence on the repurchase intention of beverage retail MSME consumers. THIRST in Bogor Regency. Meanwhile, the digital marketing variable partially does not have a significant effect on the repurchase intention of HAUS beverage retail MSME consumers in Bogor Regency.